Efficacy of Articaine versus Lignocaine as Local Anesthetic Agents Using Buccal Infiltration Technique for Extraction of Mandibular Premolars - Deepak Kolte; Harjit Singh Kalsi; Viraj Rajeev Kharkar; Tejal Patil; Barun Kumar; Ashvin Wagh; Sanpreet Singh Sachdev (Journal of Pharmacy and Bioallied Sciences)
Introduction: Lignocaine, commonly used for local anesthesia, often results in discomfort during mandibular premolar extractions due to limited tissue diffusion with the buccal infiltration technique. Articaine, with better lipid solubility, promises improved diffusion and patient comfort. This study compares the efficacy of 2% Lignocaine and 4% Articaine in reducing pain during mandibular premolar extractions. Methodology: A split-mouth, randomized, controlled trial included 40 patients, aged between 18 and 40 years, undergoing bilateral mandibular premolar extractions. Each patient received 4% Articaine with adrenaline and 2% Lignocaine with adrenaline on opposite sides at separate appointments. Pain was assessed using the Visual Analog Scale (VAS) and Faces Pain Scale (FPS). Results: Patients in the Articaine group reported significantly lower pain levels (mean FPS: 0.2) compared to the Lignocaine group (mean FPS: 3.6) (P < 0.001). In the Articaine group, 34 out of 40 patients experienced no pain, whereas all patients in the Lignocaine group reported mild to severe pain. Mild pain was reported by 23 patients in the Lignocaine group, and moderate pain by 12 (P < 0.05). No severe pain was recorded in the Articaine group. Conclusion: Articaine demonstrated superior pain control, making it a more effective choice over Lignocaine for mandibular premolar extractions using the buccal infiltration technique.